การประเมินลักษณะรากข้าวในประชากรชั่วที่ 2 จากคู่ผสมระหว่างข้าวนาสวนและข้าวไร่ - ผลวงษ์ กฤษฎาพร; ศรีวงศ์ชัย ธานี; และศรีพิจิตต์ ประภา; ม้าลำพอง เชนษฏ์ (Thai Journal of Science and Technology, 2018)
Abstract Good root traits are targeted phenotypes for improving rice yield under drought condition. The shallow-rooting rice cultivars with good economic trait could be improved root system architecture for drought tolerance. In this study, the root traits were evaluated in 126 F2 progenies derived from a cross between lowland rice, RD49 and upland rice, Prayaleumgang (PLG) rice varieties. The parental varieties and F2 progenies were evaluated for shallow root number (SRN), deep root number (DRN), total root number (TRN) and ratio of deep rooting (RDR) using the basket method. The result showed that PLG had higher DRN and RDR than RD49 but lower shallow SRN than RD49. The TRN was not significantly different between PLG and RD49. In F2 population, SRN, DRN, TRN and RDR ranged from 5 to 153, 4 to 106, 9 to 210 roots and 8.0 to 65.5 percent, respectively. SRN, TRN and RDR showed normal distribution and transgressive segregation in the F2 population. Thus, the rice lines carrying high ratio of deep rooting and total root number can be selected in this segregating population. Keywords: rice; root system; drought tolerant; total root number; ratio of deep rooting